2020
DOI: 10.30773/pi.2020.0170
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cognitive Training in a Day Care Center in Patients with Early Alzheimer’s Disease Dementia: A Retrospective Study

Abstract: Objective This study aimed to evaluate the effect of cognitive training programs on the progression of dementia in patients with early stage Alzheimer’s disease dementia (ADD) at the day care center.Methods From January 2015 to December 2018, a total of 119 patients with early ADD were evaluated. All subjects were classified into two groups according to participate in cognitive training program in addition to usual standard clinical care. Changes in scores for minimental status examination-dementia screening (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Several different types of psychosocial interventions were identified as a single or combined interventions ( Table 2 ). Nature based interventions representing the person’s experience or understanding of their own natural world included: green care farm [ 28 , 29 ], farm based [ 30 , 31 ] garden based [ 32 ] meaning in life in general [ 33 ].Memory/cognitive-based interventions related to reminiscence structured sessions [ 34 , 35 ], life story interviews [ 36 ], life review programme[ 37 ], life story work [ 38 ], emotional therapy [ 39 ] and cognitive behavioural therapy [ 40 , 41 ] Combined approaches included combined cognitive training, music and art therapy [ 42 ] combined environmental barriers and cognitive behavioural therapy [ 43 ] and combined reality orientation and cognitive behavioural therapies [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Several different types of psychosocial interventions were identified as a single or combined interventions ( Table 2 ). Nature based interventions representing the person’s experience or understanding of their own natural world included: green care farm [ 28 , 29 ], farm based [ 30 , 31 ] garden based [ 32 ] meaning in life in general [ 33 ].Memory/cognitive-based interventions related to reminiscence structured sessions [ 34 , 35 ], life story interviews [ 36 ], life review programme[ 37 ], life story work [ 38 ], emotional therapy [ 39 ] and cognitive behavioural therapy [ 40 , 41 ] Combined approaches included combined cognitive training, music and art therapy [ 42 ] combined environmental barriers and cognitive behavioural therapy [ 43 ] and combined reality orientation and cognitive behavioural therapies [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Whereas programmes focused on the use of GCFs to promote physical activities [ 30 ] and the use of a six-week programme of weekly gardening session [ 32 ]. Memory/cognitive-based interventions that were time limited ranged from five days [ 40 ], two weeks [ 37 ], four weeks [ 33 , 34 ], six weeks [ 36 ], eight weeks [ 42 ] and 12 weeks [ 41 ]. Other programmes ran for over 12months [ 40 , 44 ], over two years [ 38 ] or were open-ended [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 14 , 15 However, this does not necessarily deduce that the provision of daycare facilities will automatically lead to positive outcomes in the older population, especially because there are barriers to the uptake of such services. Studies in the United States and South Korea have demonstrated that using daycare services is more common among people with high care needs, particularly those with dementia 16 - 18 ; nevertheless, people with relatively low care needs reportedly attain the greatest improvement in well-being from daycare attendance. 19 Further, studies have revealed that older people’s lack of awareness regarding daycare is the most prevalent barrier to such services’ uptake.…”
Section: Literature Reviewmentioning
confidence: 99%